I think that answer would be C
Answer:
Step-by-step explanation:
(f+g)(x) = f(x) + g(x) = 3x-1 +x²-6
(f+g)(x) = x² +3x -5 .....( answer : B )
Answer:
The standard deviation of the sampling distribution of sample means would be 0.8186.
Step-by-step explanation:
We are given that
Mean of population=23.2 pounds
Standard deviation of population=6.6 pounds
n=65
We have to find the standard deviation of the sampling distribution of sample means.
We know that standard deviation of the sampling distribution of sample means
=![\frac{\sigma}{\sqrt{n}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csigma%7D%7B%5Csqrt%7Bn%7D%7D)
Using the formula
The standard deviation of the sampling distribution of sample means
=![\frac{6.6}{\sqrt{65}}](https://tex.z-dn.net/?f=%5Cfrac%7B6.6%7D%7B%5Csqrt%7B65%7D%7D)
![=0.8186](https://tex.z-dn.net/?f=%3D0.8186)
Hence, the standard deviation of the sampling distribution of sample means would be 0.8186.
Answer:
68 degrees
Step-by-step explanation:
Answer:
-1 / 13
Step-by-step explanation:
(x 1,y1) = (-10,5)
(x2, y2) = (3,4)
y2 - y1 / x2 - x1